2016
DOI: 10.1063/1.4951763
|View full text |Cite
|
Sign up to set email alerts
|

The effect of turbulent velocity fluctuations on the convective heat transfer to droplets subjected to evaporation and thermolysis

Abstract: Abstract. The effect of turbulent velocity fluctuations on the convective heat transfer to single droplets in a turbulent channel flow are investigated numerically. It is found that for properties relevant to typical liquid spray applications, the convective heat transfer is enhanced with increasing droplet size and bulk Reynolds number. The combined effect of convective heat transfer enhancement and increased driving forces for heat and mass transfer due to droplet dispersion is thereafter investigated for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…T A is the external fluid temperature and T S is the solid surface temperature. In the actual convection heat transfer process in the fabric surface, there will be a great effect 29 : the temperature, humility and velocity of air near the fabric surface are changing all the time, especially in the stable drying period, and the drying rate reaches the maximum. 30,31 In this model, the effects of water evaporation are further considered; the temperature of the first layer grid in the fabric surface is adopted as the external fluid temperature and then this temperature is updated with time iteration, which further enhances the accuracy of the computing method of the convective heat transfer in the fabric surface…”
Section: Fabric Heat Transfer Modelmentioning
confidence: 99%
“…T A is the external fluid temperature and T S is the solid surface temperature. In the actual convection heat transfer process in the fabric surface, there will be a great effect 29 : the temperature, humility and velocity of air near the fabric surface are changing all the time, especially in the stable drying period, and the drying rate reaches the maximum. 30,31 In this model, the effects of water evaporation are further considered; the temperature of the first layer grid in the fabric surface is adopted as the external fluid temperature and then this temperature is updated with time iteration, which further enhances the accuracy of the computing method of the convective heat transfer in the fabric surface…”
Section: Fabric Heat Transfer Modelmentioning
confidence: 99%
“…Guo et al (2015) performed numerical investigations of a urea-spray and found that failure to resolve the turbulent velocity fluctuations of the droplet phase may have significant effects on the rate of urea thermolysis and the temperature at which it occurs. Given the importance of turbulent fluctuations on the development of the urea spray (Berlemont et al , 1995; Ström et al , 2009), also the effects of the fluctuations on the turbulence-chemistry interaction could be expected to be significant.…”
Section: Introductionmentioning
confidence: 99%
“…4 The authors investigate the effects of turbulent flows and flow velocities on convective heat transfer at individual droplets in a turbulent channel flow. 4 Numerical analysis 6 has shown that air parameters (velocity and temperature), as well as in Guo et al 7 fabric velocity, are the most influential parameters on the drying rate and fabric surface temperature in the continuous drying process. It is shown that optimal values of parameters can decrease energy usage by 27.8%.…”
mentioning
confidence: 99%